Longitudinal observational research study: establishing the Australasian Congenital Cytomegalovirus Register (ACMVR) - Valerie Sung; Hayley Smithers Sheedy; Asha C Bowen; Cheryl A Jones; Elizabeth Wilson; Alanna N Gillespie; Pamela Palasanthiran; Pam Rogers; Julia E Clark; Hayley Smithers-Sheedy; Emma Waight; Asha Bowen; et al. (BMJ Open)
Purpose Congenital cytomegalovirus (cCMV) is an important cause of long-term childhood disability. In Australia, the identification and treatment practices and the long-term clinical and neurodevelopmental outcomes of children with cCMV are unknown. The Australasian cCMV Register (ACMVR) is a longitudinal register and resource for research that aims to describe and explore, in Australian children with cCMV: (1) their clinical characteristics over time, (2) antiviral therapy use/prescribing up to 1 year of age and (3) risk factors and potential avenues for prevention of adverse sequelae of the virus.Participants Children <18 years, with confirmed or probable cCMV infection, identified via medical records, community referral and physician referrals, in states with active study sites, are eligible for inclusion. The consent process is site-specific, reflecting local requirements and including both explicit consent and opt-out models. Participation in the ACMVR allows local site researchers to (1) collect specified demographic and clinical data from medical records, health professionals and families, (2) recontact parents/guardians to undertake developmental screening for their child at time-points up to 5 years of age, (3) share information with parents/guardians about relevant ethically approved research studies and (4) include participant data in ethically approved data linkage studies.Findings to date Ethics and governance approvals, study database and a steering group have been established. Data collection is active in five sites across Australia.Future plans The ACMVR will inform our understanding of the long-term outcomes for children with cCMV in Australia and provide a sampling frame and resource for recruitment in future clinical and epidemiological research to inform practice and policy. New opportunities for the establishment of additional study sites and collaborations with Australian maternity and fetal medicine researchers and with cCMV registries in other countries are currently being explored.